ヒガシ ナンキョク ミズホコウゲン ニ オケル クッセツホウ オヨビ コウカク ハンシャホウ ジシン タンサ カンソク ガイヨウ (ダイ43ジ ナツタイ ホウコク) - 宮町, 宏樹; ミヤマチ, ヒロキ; 戸田, 茂; トダ, シゲル; 松島, 健; マツシマ, タケシ; 高田, 真秀; タカダ, マサミツ; 高橋, 康博; タカハシ, ヤスヒロ; 神谷, 大輔; カミヤ, ダイスケ; et al. (国立極地研究所, 2003)
P(論文) 第43次日本南極地域観測隊夏隊(JARE-43)では,東南極みずほ高原において,JARE-41に引き続き,みずほ高原下の地殻の速度構造を明らかにするため,屈折法および広角反射法地震探査を実施した.探査測線は,みずほルート上のH176地点を起点に北北東方向に101 km,南南西方向に50 kmの測線長約151 kmであり,JARE-41の探査測線と斜交している.この測線上に161台の地震観測点を配置し,7カ所で薬量700 kg程度の大発破,1カ所で薬量20 kgの小発破を行った.大発破点からの距離が100 km以下では,明瞭な初動が観測された.また,氷床中を伝播して来た波,分散波および地殻深部(コンラッド面とモホ面)からの反射波と推定される後続波も観測された.発破点近傍の観測で得られた初動走時から,氷床が厚さ36-45 mでみかけ速度2.7-2.9 km/sの上部層とみかけ速度3.7-3.9 km/sの下部層から成り立つことが推定された.測線全体の初動走時からは,氷床直下の基盤層(岩盤)のみかけ速度が,測線の北部では5.9 km/s,中央部～南部では6.1-6.2 km/sとなり,基盤層の速度差が示唆された.本報告は,実験の概要と得られたデータについて述べる. A seismic refraction and wide-angle reflection exploration was successfully conducted along a profile crossing the JARE-41 seismic profile on the Mizuho Plateau, in East Antarctica, in the austral summer season of 2001-2002 (JARE-43). One hundred sixty-one seismic stations were temporarily installed along a profile about 151 km long and seven large shots with about 700 kg of dynamite were fired. In addition, one shot with charge size of 20 kg was also arranged along the profile. The obtained seismic records show the clear onsets of the first arrivals at distances of less than 100 km from each large shot. In particular, seismic waves traveling through the ice sheet and dispersed surface waves were clearly observed. Some later reflection phases were also detected. The obtained first travel time data show that the ice sheet is a two-layered structure consisting of an upper layer with a P wave velocity of 2.7-2.9 km/s and a lower layer of 3.7-3.9 km/s. The thickness of the upper layer is estimated to be about 36-45 m. The apparent velocity in the basement rock just beneath the ice sheet is 6.1-6.2 km/s in the central and southern parts of the profile and almost 5.9 km/s in the northern part. This report describes basic outlines of the exploration and the obtained seismic data. departmental bulletin paper